2016
DOI: 10.1017/s1479262116000071
|View full text |Cite
|
Sign up to set email alerts
|

Role of genetic resources and molecular markers inMucuna pruriens(L.) DC improvement

Abstract: Mucuna pruriens (L.) DC is a tropical legume cover crop with promising nutritional and agronomic potentials. It is also a key source of 3,4 dihydroxy-L-phenylalanine (L-Dopa) – a precursor of dopamine used in the treatment of Parkinson's disease. However, lack of well-characterized germplasm plus poor accessibility to genomic resources has hindered its breeding programs. Furthermore, the cause and effect of various biotic and abiotic stresses impacting yield is also little studied. Systematic collection and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…In a predominantly self-pollinating species like M. pruriens, we expect lower levels of genetic diversity. But higher values recorded here and in some earlier studies (summarized inSathyanarayana et al 2016) categorically points to presence of out-crossing in this species as observed initially byPadmesh et al (2006). This is partly supported by a high average gene ow among the population groups (Nm = 3.03).…”
supporting
confidence: 79%
“…In a predominantly self-pollinating species like M. pruriens, we expect lower levels of genetic diversity. But higher values recorded here and in some earlier studies (summarized inSathyanarayana et al 2016) categorically points to presence of out-crossing in this species as observed initially byPadmesh et al (2006). This is partly supported by a high average gene ow among the population groups (Nm = 3.03).…”
supporting
confidence: 79%
“…Mucuna pruriens (L.) DC. (velvet bean) is reported to be native to China and East India [ 5 ] but has now attained a pantropical distribution with a major niche in the Indian sub-continent [ 6 ]. Like common bean and mung bean, velvet bean has a chromosome number of 2n = 2x = 22 [ 7 ], but with a much larger estimated genome size of between 1,281 to 1,361 Mbp/C (A.N.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of genomic tools that can aid in developing molecular markers, genetic maps etc., the genetic improvement of underutilized crops has been greatly facilitated, enabling the development of improved genotypes or varieties with enhanced trait values [ 21 , 22 ]. However, studies focusing on the development of genomic resources of M. pruriens are lacking, with only a few reports available on the use of molecular markers such as RAPDs and AFLPs (reviewed in [ 6 ]). In recent years, transcriptome sequencing has emerged as an efficient method to generate genomic-level data, large expressed sequence tag (EST) sequences, and molecular markers.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been found to reactivate the antioxidant defence system, necessary for maintaining homeostasis within the body. For further details, see Sathyanarayana et al (2016).…”
Section: Mucuna Pruriens (L) DC Velvet Beanmentioning
confidence: 99%